From Marcos to Aquino Governments: State Sponsorship of Diaspora Philanthropy - Duaqui, Yellowbelle d.M. (Philippine Social Sciences Review; Vol. 65 No. 2 July-Dec 2013, Ed. Rolando Esteban, 2014)
The paper probes into labor migration policies and the evolution of discourses nested in these policies as endorsements of diaspora philanthropy. It reviews government policies on labor migration and diaspora philanthropy and makes sense of the contents of these policies through frame and discourse analyses. Neoliberalism permeates Philippine migration policy-making, positions Filipino labor migration as a crucial national development strategy, and diaspora philanthropy as its byproduct. The “OFWs as Modern-day Heroes Frame” powers and sustains diaspora philanthropy through volunteering, fund-raising, and other practices, to help promote local development. State sponsorship may help explain diaspora philanthropy despite the deterritorialized nature of the phenomenon, which, in turn, appears to contribute to nation-building.
Keywords: migrant giving, diaspora philanthropy, state sponsorship, deterritorialization, transnationalism